2021
DOI: 10.1111/joim.13231
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in COVID‐19 interstitial pneumonia

Abstract: Background Published reports on tocilizumab in COVID‐19 pneumonitis show conflicting results due to weak designs or heterogeneity in critical methodological issues. Methods This open‐label trial, structured according to Simon's optimal design, aims to identify factors predicting which patients could benefit from anti‐IL6 strategies and to enhance the design of unequivocal and reliable future randomized trials. A total of 46 patients with COVID‐19 pneumonia needing of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Moreover, non-specific immune-regulatory strategies, such as injection of systemic glucocorticosteroids, intravenous immunoglobulins (IVIG), and convalescent serum therapy can also be administered. Pilot studies have shown the life-saving efficacy of IL-6-blocking monoclonal antibodies and reducing the hospitalization period in severe COVID-19 patients with ARDS (61) and several clinical trials are evaluating the safety and efficacy of IL-6 blocking agents to repress the hyperinflammatory condition in hospitalized COVID-19 patients, which are described in Table 1 . Here, we discuss different methods for inhibiting the IL-6 pathway at different stages based on recently published data and clinical trials to develop bench-to-bedside guidance to improve the clinical outcome of the patients.…”
Section: Inhibition Of Il-6 In Covid-19mentioning
confidence: 99%
“…Moreover, non-specific immune-regulatory strategies, such as injection of systemic glucocorticosteroids, intravenous immunoglobulins (IVIG), and convalescent serum therapy can also be administered. Pilot studies have shown the life-saving efficacy of IL-6-blocking monoclonal antibodies and reducing the hospitalization period in severe COVID-19 patients with ARDS (61) and several clinical trials are evaluating the safety and efficacy of IL-6 blocking agents to repress the hyperinflammatory condition in hospitalized COVID-19 patients, which are described in Table 1 . Here, we discuss different methods for inhibiting the IL-6 pathway at different stages based on recently published data and clinical trials to develop bench-to-bedside guidance to improve the clinical outcome of the patients.…”
Section: Inhibition Of Il-6 In Covid-19mentioning
confidence: 99%
“…CoV-2 pandemic, IL-6 blockade using monoclonal antibodies was investigated with potential benefits described in several observational or cohort studies [105,127,131,[158][159][160][161]. However, some contrasting data from RCTs with the IL-6 R blocker tocilizumab have raised questions on the real usefulness of these drugs and posed some questions about the real role played by IL-6 in severe COVID-19 [10,139,140,142,143,162,163].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Recently, we demonstrated that serum levels of microRNAs involved in the modulation of inflammation ( Olivieri et al, 2021 , Olivieri et al, 2013 ), were associated with the clinical response to anti-IL-6 receptor therapy in a sample of COVID-19 patients ( Pomponio et al, 2021 , Sabbatinelli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%